Limitations in Validating Derived Soil Water Content from Thermal/Optical Measurements Using the Simplified Triangle Method - Kasim, Abba Aliyu; Carlson, Toby Nahum; Usman, Haruna Shehu (MDPI (Multidisciplinary Digital Publishing Institute), 2020)
We assess the validity of the surface moisture availability parameter (Mo) derived from satellite-based optical/thermal measurements using the simplified triangle method. First, we show that Mo values obtained from the simplified triangle method agree closely with those generated from a soil/vegetation/atmosphere/transfer (SVAT) model for scenes over a field site at the Allahabad district, India. Next, we compared Mo values from the simplified triangle method for these same overpass scenes with surface soil water content measured at depths of 5 and 15 cm at this field site. Although a very weak correlation exists between remotely sensed values of Mo for the full scenes and measured soil water content measured at both depths, correlations increasingly improve for the 5 cm samples (but not for the 15 cm samples) as pixels were limited to increasingly smaller vegetation fractions. We conclude that the simplified triangle method would yield reasonable values of Mo and demonstrate good agreement with ground measurements, provided that validation is limited to pixels with little or no vegetation and to soil depths of 5 cm or less.
Remote Sens. 2020, 12(7), 1155;
Keywords: simplified triangle method; soil water content; satellite-based optical/thermal measurement; limitation; validating; CDA; Nigeria; Bayero University, Kano